Synergistic effect of high-intensity focused ultrasound and low-fluence Q-switched Nd:YAG laser in the treatment of the aging neck and décolletage. Issue 1 (January 2017) - Nam, Jae-Hui; Choi, Young-Jun; Lim, Jae; Min, Joon; Kim, Won-Serk
Abstract High-intensity focused ultrasound (HIFU) is regarded as an effective skin-lifting device; however, literature regarding treatment of the aging neck and décolletage with HIFU is scarce. Our study aimed to evaluate the efficacy of combination with HIFU and low-fluence Q-switched Nd:YAG (LQSNY) laser on the aging neck and décolletage. Nineteen women were assessed. HIFU at two visits and LQSNY laser at six visits were used to irradiate the neck and chest. At week 16, improvements were rated using the Dedo classification, Fabi/Bolton Chest Wrinkle Scale (FBCWS), and Global Aesthetic Improvement Scales (GAIS). Erythema and melanin indices (EMIs) and cervicomental angle were measured. Subject GAIS and satisfaction were evaluated at follow-up visits. At week 16, neck sagging and chest rhytides were improved on Dedo classification and FBCWS, respectively. Pigmentation and rhytides of the neck and chest were rated as improved in 30 % or more of the subjects by physician GAIS and in approximately 80 % of the subjects by subject GAIS. The above differences seemed to be attributable to the initial expectation level and mild severity pertaining to dress custom in Korea. Eighty-four percent of subjects were satisfied with treatment outcomes. EMIs were decreased on the chest. The combination of HIFU and LQSNY is an effective treatment option to mitigate rhytides and pigmentation of the neck and décolletage.